(untitled) (Revista Rupturas, 2020)
This paper exposes part of the data developed in the chapter related to sociodemographic context, in the doctoral "The coloniality of being in the performative practices of migrant women, workers, and heads of household for the support of the lives of their own families. A research in San Jose, Costa Rica. This article shows data from the sociodemographic context chapter of the doctoral thesis entitled,”. The analysis focuses on the conditions of the social organization of care in Costa Rica, and explains the crisis generated by the lack of social co-responsibility on carework in the country. Situation that generates tensions within households, and has a direct effect mainly in women, and particular in migrant Nicaraguan female heads of household.